Regular Student Social Acceptance of Inclusive Students and Inclusion of Student's Confidence and Implications for Counseling Services - Zulfriadi Tanjung; Afrizal Sano; Zadrian Ardi (Jurnal Neo Konseling, 2020)
Social acceptance in the education process should be able to run well, but in reality there are problems. Inclusive Students get less social acceptance from Regular Students this results in decreased confidence of Inclusive Students. One of the factors influencing the Inclusive Students' self-confidence is social acceptance, therefore, if social acceptance is low, the self-confidence of Inclusion Students is low and vice versa.This article is a literature study that will explain the Regular Students 'social acceptance of Inclusive Students and the Inclusive Students' confidence and their implications for guidance and counseling services. The data source in this article comes from books, articles, research report and written regulations which regulate inclusive education.  Hopefully this article can be a reference.